FAKTOR - FAKTOR YANG MENDORONG KEPATUHAN MASYARAKAT KABUPATEN BANTUL UNTUK MEMBAYAR PBB P2 - Dewi, Septian Kurnia; Hidayatulloh, Amir (EL MUHASABA: Jurnal Akuntansi (e-Journal), 2020)
The purpose of this study was to analyze the influence of motivation, morality, and the role of village officials on community compliance in paying rural and urban land and building taxes with tax sanctions as a moderating variable. The population in this study is individual taxpayers who live in Bantul Regency, Yogyakarta Special Region Province. The sample in this study is an individual taxpayer who owns land and buildings domiciled in Bantul Regency. The sampling technique in this study uses purposive sampling, with criteria (1) taxpayers who live in Bantul Regency, and (2) taxpayers who own land and buildings. Data collection in this study used a questionnaire distributed directly to respondents who met the criteria. Respondents in the study numbered 127 respondents. Data analysis techniques in this study used simple regression and Moderated Regression Analysis. This study found that community compliance to pay PBB P2 was influenced by the motivation and role of village officials. Meanwhile, morality has no effect on community compliance to pay PBB P2. The study also obtained the results of the taxation sanski variable moderating the influence of motivation on taxpayer compliance, and moderating the effect of the role of village officials on tax compliance. However, tax sanctions do not moderate the effect of morality on taxpayer compliance to pay PBB P2.